2013
DOI: 10.1590/s0004-28032013000400013
|View full text |Cite
|
Sign up to set email alerts
|

First Single-Port Laparoscopic Pancreatectomy in Brazil

Abstract: -Context -Pancreatic surgery is an extremely challenging field, and the management of pancreatic diseases continues to evolve. in the past decade, minimal access surgery is moving towards minimizing the surgical trauma by reducing numbers and size of the port. in the last few years, a novel technique with a single-incision laparoscopic approach has been described for several laparoscopic procedures. Objectives -We present a single-port laparoscopic spleen-preserving distal pancreatectomy. To our knowledge, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Recently, three more cases were performed in our department. Now, during the 29 cases, transumbilical single-incision laparoscopy spleen-preserving distal pancreatectomy in 16 cases and single-incision laparoscopy distal pancreatectomy without splenic preservation in 13 case were performed, and the patients’ postoperative recoveries were all uneventful [ 6 13 ]. Now, these experiences well confirm the feasibility and safety of the TUSI-LDP in selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, three more cases were performed in our department. Now, during the 29 cases, transumbilical single-incision laparoscopy spleen-preserving distal pancreatectomy in 16 cases and single-incision laparoscopy distal pancreatectomy without splenic preservation in 13 case were performed, and the patients’ postoperative recoveries were all uneventful [ 6 13 ]. Now, these experiences well confirm the feasibility and safety of the TUSI-LDP in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, for further minimizing surgical trauma by reducing the number of the port, many experienced laparoscopic surgeons have tried to develop a new minimally invasive technique called “single incision laparoscopic surgery” (SILS), which has been now successfully and widely applied in many fields of abdominal surgery [ 4 , 5 ]. However, The SILS performed on the pancreatic lesions has been reported only recently, and the experience is still limited now [ 6 13 ]. Therefore, more studies are still required to confirm the feasibility of transumbilical single-incision laparoscopic distal pancreatectomy (TUSI-LDP).…”
Section: Introductionmentioning
confidence: 99%
“…It is especially used in young female due to the good cosmetic results. Single-incision laparoscopic procedure is less invasive than standard multiport laparoscopy but may have unique difficulties for the laparoscopic surgeon 12 , 13 . First, retraction is significantly limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, a novel technique with a single-incision laparoscopic approach has been described 3 . This technique has mainly been used for laparoscopic cholecystectomy, but recent reports showed feasibility even in more complex operations such as gastric, liver and pancreas resection 12 , 13 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is interesting to note that a spleenpreserving procedure was performed even in 46 patients (78%). A summary of perioperative outcomes showed that 20 patients were male, and 37 were female with a mean age of 45.9 ±16.0 years (gender information was missing in one report 13 ). Most pathologic diagnoses were benign or borderline malignant tumors of the pancreas with a mean tumor diameter of 3.4±1.6 cm.…”
Section: Currently Available Surgical Platforms and Short-term Outcomesmentioning
confidence: 99%